The Need for "Un-consolidating" Consolidated Banks' Stress Tests - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2012)
The recent crisis has spurred the use of stress tests as a (crisis) management and early warning tool. However, a weakness is that they omit potential risks embedded in the banking groups' geographical structures by assuming that capital and liquidity are available wherever they are needed within the group. This assumption neglects the fact that regulations differ across countries (e.g., minimum capital requirements), and, more importantly, that home/host regulators might limit flows of capital or liquidity within a group during periods of stress. This study presents a framework on how to integrate this risk element into stress tests, and provides illustrative calculations on the size of the potential adjustments needed in the presence of some limits on intragroup flows for banks included in the June 2011 EBA stress tests.